Phosphorylation of a NAC Transcription Factor by a Calcium/Calmodulin-Dependent Protein Kinase Regulates Abscisic Acid-Induced Antioxidant Defense in Maize. Issue 3 (10th May 2016) - Zhu, Yuan; Yan, Jingwei; Liu, Weijuan; Liu, Lei; Sheng, Yu; Sun, Yue; Li, Yanyun; Scheller, Henrik Vibe; Jiang, Mingyi; Hou, Xilin; Ni, Lan; Zhang, Aying
Abstract : The maize protein kinase ZmCCaMK phosphorylates the ZmNAC84 transcription factor at Ser113 during abscisic acid-induced antioxidant. Abstract: Calcium/calmodulin-dependent protein kinase (CCaMK ) has been shown to play an important role in abscisic acid (ABA )-induced antioxidant defense and enhance the tolerance of plants to drought stress. However, its downstream molecular events are poorly understood. Here, we identify a NAC transcription factor, ZmNAC84, in maize ( Zea mays ), which physically interacts with ZmCCaMK in vitro and in vivo. ZmNAC84 displays a partially overlapping expression pattern with ZmCCaMK after ABA treatment, and H2 O2 is required for ABA-induced ZmNAC84 expression. Functional analysis reveals that ZmNAC84 is essential for ABA-induced antioxidant defense in a ZmCCaMK-dependent manner. Furthermore, ZmCCaMK directly phosphorylates Ser-113 of ZmNAC84 in vitro, and Ser-113 is essential for the ABA-induced stimulation of antioxidant defense by ZmCCaMK. Moreover, overexpression of ZmNAC84 in tobacco ( Nicotiana tabacum ) can improve drought tolerance and alleviate drought-induced oxidative damage of transgenic plants. These results define a mechanism for ZmCCaMK function in ABA-induced antioxidant defense, where ABA-produced H2 O2 first induces expression of ZmCCaMK and ZmNAC84 and activates ZmCCaMK. Subsequently, the activated ZmCCaMK phosphorylates ZmNAC84 at Ser-113, thereby inducing antioxidant defense by activating downstream genes.